Kennzahlensysteme in tqm-geführten unternehmen - Jankalová, Miriam (Univerzita Pardubice, 2009)
On the end of twentieth century began increasingly associate the successfulness of business with the term quality. Is any method, technique; through whose is it possible to evaluate the reached level of business successfulness and excellence of TQM enterprises? The answer is: the individual system of indicators.
Keywords: TQM; scorecard; indicators; Balanced ScoreCard; enterprises